(untitled) (Research, Society and Development, 2025)
This research aims to analyze the impact of educational management on the results of national tests in a district of the Dominican Republic during the period 2023. This is a documentary type with a non-experimental design and a qualitative approach, where it was used as a technique Data collection included document analysis and bibliographic review, with the instruments used being records and research diaries. For this, the actions carried out by the management team for the development of the national testing process and the results obtained by the district’s students were considered.